An Arnold DCT based Non-Blind Watermarking Technique for Medical Images - Venkateswarlu, Lendale; Vyagreswara Rao, N; Eswara Reddy, B (International Journal of Computer Sciences and Engineering, 2025)
Telemedicine is a blend of medical information system and information technology that incorporates the transmission of medical data over the internet. The potential difficulties involved in implementation are confidentiality, robustness against attacks and integrity. In this paper, a dual-transform domain watermarking model has been proposed based on Arnold transform used for spatial de-correlation of the host image applied after Discrete Cosine Transform domain-based watermark insertion. The salient feature of this method is to accomplish improved robustness while safeguarding the originality of the image. This paper attempts to substantiate the guaranteed features by simulating the quality metrics on the benchmark images (MRI, X-Ray and US-Scan). The consequences of examinations have been exhibited through quality measures such as Structural Similarity Index (SSIM), Normal Cross Correlation (NCC) and Peak Signal-to-Noise Ratio (PSNR).